Regional Planning Framework for Addressing Flood Vulnerability of a Metropolitan Region: The Case of Malappuram, Kerala, India - Robin K; Mohammed Firoz C; Sruthi Krishnan V (Journal of Regional and City Planning, 2023)
Flood susceptibility is becoming increasingly important among the various natural disasters in terms of environmental, economic, and social consequences. The eco-regional planning approach, which incorporates the ecological boundary as a layer in the spatial planning process of settlements, is one of the most innovative concepts in recent research to address these problems. Hence, this research interrogated flood susceptibility mapping tools using an appropriate model for better settlement planning and management. A frequency ratio model was applied to a case region, Malappuram (in  the State of Kerala, India), one of the world’s fastest urbanizing metropolitan regions, using a three-tier assessment framework. A frequency ratio database for flood susceptibility mapping was created by combining historic flood locations with independent factors. The study region was divided into five flood-risk zones based on the computed flood susceptibility index, which varied from 0 to 18.38, i.e., very high, high, moderate, low, and very low. The results showed that the high and very high susceptibility classes accounted for 8.82% and 17.17% of the land, respectively. This paper highlights the requirement for a multi-level assessment of an ecologically oriented regional planning regime in India and estimates the success rate of flood prediction at 79.33%. The proposed regional planning framework is therefore essential for local government planners, researchers, and administrators when creating flood mitigation measures, and has the potential to become a substantial and essential instrument.